Pengaruh Model Pembelajaran Guided Discovery Learning Terhadap Hasil Belajar Matematika Siswa Kelas III di SDN 07 Pontianak Kota (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to test the influence of the Guided Discovery Learning learning model on the mathematics learning outcomes of grade III students at SDN 07 Pontianak Kota. The method used is an experiment with a quasi-experimental approach, where the free variable is the Guided Discovery Learning (X) model and the bound variable is the learning outcome of grsade III students (Y). The research sample consisted of 38 students in grade III of SDN 07 Pontianak Kota, class IIIA as the control class and class IIIB as the experimental class. Data was collected through Pretest and Posttest tests in each class. The resulting data was analyzed using statistical tests. The pretest and posttest scores showed that the Guided Discovery Learning model had a positive effect on learning outcomes, in the experimental class the average score of the pretest was 60.9 and the posttest was 74.7, while in the control class, the average score of the pretest was 58.2 and the posttest was 64.2. The results of the hypothesis test also showed Sig. (2-tailed) values of 0.009 and 0.007, which means that H_a was accepted and H_o rejected. It was concluded that the Guided Discovery Learning learning model in the experimental class showed a better improvement in learning outcomes compared to the control class. This difference shows that the guided discovery learning model has a positive influence on students' Mathematics learning outcomes in Grade III SDN 07 Pontianak Kota